Listening out for God’s Breath – a Negative Hermeneutical Approach to Mysticism - Wolff, Edda (Interdisciplinary journal for religion and transformation in contemporary society, 2024)
This essay argues that a negative hermeneutics, i.e., a hermeneutics that takes its starting point from the experience of gaps, failures, and limits, is a suitable lens for the study of mysticism. It uses the concept of travail of the negative, which focuses on dynamics of a continuous ‘unsaying’ and ‘subverting’ of traditional expressions of faith and religious practice, to explore the connection between aspects of practical and theoretical negativity in mystical expressions. It suggests that this approach to mystical theology makes an important contribution to the wider theological discourse and encourages theology to take the fundamental character of negation seriously.